Tell the Difference Between Mitosis and Meiosis: Interplay Between Chromosomes, Cytoskeleton, and Cell Cycle Regulation - Sato, Masamitsu; Kakui, Yasutaka; Toya, Mika (Frontiers in Cell and Developmental Biology, 2021)
Meiosis is a specialised style of cell division conserved in eukaryotes, particularly designed for production of gametes. A huge number of studies to date have demonstrated as to how chromosomes behave and how meiotic events are controlled. Yeast substantially contributed to understanding of molecular mechanisms of meiosis in the past decades. Recently, evidence began to accumulate to draw a perspective landscape showing that chromosomes and microtubules are mutually influenced: microtubules regulate chromosomes, whereas chromosomes also regulate microtubule behaviours. Here we focus on lessons from recent advancement in genetical and cytological studies of the fission yeast Schizosaccharomyces pombe, revealing how chromosomes, cytoskeleton and cell cycle progression are organised and particularly how these are differentiated in mitosis and meiosis. These studies illuminate that meiosis is strategically designed to fulfil two missions: faithful segregation of genetic materials and production of genetic diversity in descendants, through elaboration by meiosis-specific factors in collaboration with general factors.